Accelerating strain engineering in biofuel research via build and test automation of synthetic biology. (February 2021) - Zhang, Jianzhi; Chen, Yongcan; Fu, Lihao; Guo, Erpeng; Wang, Bo; Dai, Lei; Si, Tong
Graphical abstract: Highlights: The lack of predictive modeling limits biosystems design for biofuel production. Automation in build and test accelerates strain engineering for biofuel research. Microplates exhibit advantages and limitations in modeling feedstock-to-fuel conversion. Biofoundry enables standardization and data-driven approaches. Abstract : Biofuels are a type of sustainable and renewable energy. However, for the economical production of bulk-volume biofuels, biosystems design is particularly challenging to achieve sufficient yield, titer, and productivity. Because of the lack of predictive modeling, high-throughput screening remains essential. Recently established biofoundries provide an emerging infrastructure to accelerate biological design-build-test-learn (DBTL) cycles through the integration of robotics, synthetic biology, and informatics. In this review, we first introduce the technical advances of build and test automation in synthetic biology, focusing on the use of industry-standard microplates for DNA assembly, chassis engineering, and enzyme and strain screening. Proof-of-concept studies on prototypes of automated foundries are then discussed, for improving biomass deconstruction, metabolic conversion, and host robustness. We conclude with future challenges and opportunities in creating a flexible, versatile, and data-driven framework to support biofuel research and development in biofoundries.